Christianization as a Challenge for Islamic Daʿwah in Indonesia - Abdul Hamid; Muhammad Utsman Shalih; Badrah Uyuni (Millah: Journal of Religious Studies, 2023)
The aim of this study was to evaluate the growth and impact of Christianity as a missionary religion on the Islamic da'wah in Indonesia, where the Muslim community has a long history of resistance to colonialization, which was initiated by the Christian community. Furthermore, a qualitative descriptive method was used with data predominantly obtained through the observation of facts in the Christianization field. In addition, the effects of Christianity on the Islamic da'wah were analyzed through a review of documentation and reference studies. The results showed that some of the methods used by Christians in spreading their religion and movements were occupation, politics, Western citizens, poverty, diseases, consciousness weakness, self-preparation, Muslims' indulgence, financial guarantees, Laziness in teachings, preparing the missionaries, and brainwashing. By utilizing these methods, Christians often proclaimed their denomination and congregation, ultimately leading to various community conflicts. The findings suggest the need for a healthy and productive dialogue from a new perspective to resolve conflicts, promote harmony, and create a fairer, peaceful, and innovative civilization that views religion through spiritual perspectives.